O1 Admission avoidance in tonsillitis and peritonsillar abscess: a prospective national audit during the initial peak of the COVID-19 pandemic. (8th April 2021) - ,; Rocke, John
Abstract: Introduction: During the COVID-19 outbreak, the collaborative network for ENT trainees in the UK (INTEGRATE), conducted a multi-centre prospective audit on the management of Tonsillitis and Quinsy. This was in response to the implementation of new COVID-19 specific guidelines released by ENT UK and to explore factors relating to unscheduled re-presentations discharges direct from the Emergency Department (ED). Methods: Consecutive patients with suspected tonsillitis or quinsy, aged 18 or over, and referred to ENT in secondary care were eligible for inclusion. Data was collected, using a standardised electronic case report form, relating to patient demographics, COVID-19 status, clinicians' grade, assessment and interventions. Each case was followed-up for 10 days to assess predictors of unscheduled re-presentation after discharge direct from the ED. Results: 83 centres submitted 765 tonsillitis and 416 quinsy cases. 54.4% of tonsillitis cases and 45.3% of quinsy were discharged directly from the ED. 9.6% of tonsillitis and 10.3% of quinsy discharges re-presented within 10 days, compared to 9.7% and 10.6% for those initially admitted. IV steroids were given to 67.0% of tonsillitis patients and 73.6% of quinsy. 77.2% of quinsy patients underwent drainage during their initial presentation, but there was no significant difference in re-presentation rate in those drained vs not-drained (p = 0.85). Univariable logistic regression showed no significant predictors of re-presentation within 10 days. Conclusion: Management of tonsillitis and quinsy was affected during the initial peak of the pandemic, with a shift towards outpatient care. Some patients who may previously have been admitted to hospital may be safely discharged from the ED.